Odpowiedzi

2010-02-12T11:39:28+01:00
B) 3x + 2y = 2
+ -3x + y = 10
------------------------
3y=12
y=4

3x+8=2
y=4

x=-2
y=4

c) 3x+2y =5
+ 2x+2y =2 / *(-1)
-------------------------------
x=3
9+2y=5

x=3
y=-2


d) x+4y =11
2x+5y =10

x=11-4y
2(11-4y)+5y=10

x=11-4y
22-8y+5y=10

x=11-4y
-3y=-12

x=11-4y
y=4

x=-5
y=4


e) 4x+5y =-4 / *(-6)
6x+7y =-6 / (4)

-24x-30y=24
+ 24x+28y=-24
-----------------------------
y=0
x=-1



f) 2x-11y =73 / *(-3)
3x-4y = 47 /*(2)

-6x+33y=-219
+ 6x-8y=94
-----------------
25y=-125
y=-5

2x+55=73
y=-5

x=9
y=-5
Najlepsza Odpowiedź!
2010-02-12T11:51:29+01:00
B) 3x + 2y = 2
-3x + y = 10
3y = 12 / :3
y = 4
3x + 2 razy 4 = 2
y = 4
3x = 2 - 8
y = 4
3x = -6 / :3
y = 4
x = -2
c) 3x + 2y = 5
2x + 2 y = 2 / razy -1
3x + 2y = 5
-2x - 2y = -2
x = 3
3 razy 3 + 2y = 5
x = 3
2y = 5-9
x= 3
2y= -4 / :2
x= 3
y = -2
d) x + 4y = 11 / razy -2
2x + 5y = 10
-2x -8y = -22
2x + 5y = 10
- 3y = -12 / : -3
y = 4
x + 4razy4 = 11
y = 4
x= 11-16
y=4
x= -5

e) 4x + 5y = -4 / razy - 6
6x + 7y = -6 / razy 4
-24x - 30y = 24
24x +28y = -24
-2y = 0 / :-2
y = 0
4x + 0 = -4
y = 0
4x = -4 / :4
y=0
x= -1

f) 2x - 11y = 73 / razy - 3
3x - 4y = 47 / razy 2
-6x + 33y = - 219
6x - 8y = 94
25y = - 125 /: 25
y = -5
2x + 55 = 73
y= -5
2x= 18
y= -5
x= 9


2010-02-12T11:51:40+01:00
B) 3x + 2y = 2
-3x + y = 10
--------------
3y = 12 /:3
y = 4

3x + 2y = 2
3x + 2*4 = 2
3x + 8 = 2 / -8
3x = -6 / :3
x = -2

y = 4
x = -2

c) 3x+2y =5
2x+2y =2 / * (-1)

3x+2y =5
-2x -2y = -2
--------------
x = 3

3x+2y =5
3*3 +2y = 5
9 + 2y = 5 / -9
2y = -4 / :2
y = -2

x = 3
y = -2

d) x+4y =11 /*(-2)
2x+5y =10

-2x -8y = -22
2x + 5y = 10
----------------
-3y = -12 / :(-3)
y = 4

x+4y =11
x + 4*4 = 11
x + 16 = 11 /-16
x = -5

y = 4
x = -5

e) 4x+5y =-4 / *(-3)
6x+7y =-6 / *2)

-12x - 15y = 12
12x + 14y = -12
------------------
-y = 0 /*(-1)
y = 0

4x+5y =-4
4x + 5*0 = -4
4x = -4 /:4
x = -1

y = 0
x = -1

f) 2x-11y =73 /*(-3)
3x-4y = 47 /*2

-6x + 33y = -219
6x - 8y = 94
-------------------
25y = -125 /:25
y = -5

2x-11y =73
2x - 11*(-5) = 73
2x + 55 = 73 / -55
2x = 18 :2
x = 9

y = -5
x = 9